PEDSnet: a National Pediatric Learning Health System. (12th May 2014) - Forrest, Christopher B; Margolis, Peter A; Bailey, L Charles; Marsolo, Keith; Del Beccaro, Mark A; Finkelstein, Jonathan A; Milov, David E; Vieland, Veronica J; Wolf, Bryan A; Yu, Feliciano B; Kahn, Michael G
Abstract: A learning health system (LHS) integrates research done in routine care settings, structured data capture during every encounter, and quality improvement processes to rapidly implement advances in new knowledge, all with active and meaningful patient participation. While disease-specific pediatric LHSs have shown tremendous impact on improved clinical outcomes, a national digital architecture to rapidly implement LHSs across multiple pediatric conditions does not exist. PEDSnet is a clinical data research network that provides the infrastructure to support a national pediatric LHS. A consortium consisting of PEDSnet, which includes eight academic medical centers, two existing disease-specific pediatric networks, and two national data partners form the initial partners in the National Pediatric Learning Health System (NPLHS). PEDSnet is implementing a flexible dual data architecture that incorporates two widely used data models and national terminology standards to support multi-institutional data integration, cohort discovery, and advanced analytics that enable rapid learning.